Measuring land cover change in Seremban, Malaysia using NDVI index - Aburas, Maher Milad; Abdullah, Sabrina Ho; Ramli, Mohammad Firuz; Ash’aari, Zulfa Hanan (Elsevier, 2015)
The normalized difference vegetation index (NDVI) is one of the significant classification methods widely used in detecting land cover and land use changes. For this purpose, two Landsat TM images from 1990 to 2010 are used to extract NDVI values. The NDVI values are initially computed using the Natural Breaks (Jenks) method to classify NDVI map. Afterwards, a Difference NDVI map between 1990 and 2010 is generated to negatively or positively identify the values of land cover changes. Results confirmed that the area without vegetation, such as bodies of water, as well as built up areas and barren lands, increased from 3.55% in 1990 to 7.25% in 2010. The dense vegetation area also decreased from 78.57% to 65.44%, indicating the necessity to create new policies in the city for the protection of vegetation areas during the urban and economic development in Seremban.